Immigrants’ crimes involvement in Sabah / Suzyneta Izziyani Anwar and Haijon Gunggut - Anwar, Suzyneta Izziyani; Gunggut, Haijon (Faculty of Administrative Science and Policy Studies, 2012)
The influx of immigrants has been a long-standing issue in Sabah since the late 1970s. As immigrants’ crimes involvement often receives media’s attention, a perceived link between immigrants and crimes continues to exist. As a result, society may perceive immigrants to be prone to commit crimes, which later breeds fear and anxiety among locals (Sabahans). Yet, limited studies were conducted on this matter. This paper seeks to examine the locals’ perception towards the involvement of immigrants in crimes in Sabah. Thus, the purposes of this study are: (1) to analyze the locals’ perception towards immigrants’ crime involvement in Sabah, and (2) to identify misperceptions or misconceptions of immigrants by Sabahans in relation to crime. This paper focuses mostly on Indonesia and Filipino immigrants, as they made up the majority of immigrants in the state. As a qualitative based research, data were obtained from past research and interviews with the locals. It was found that the interviewees have a negative perception towards immigrants in term of crimes. Apart from that, the interviewees perceived that most of the crimes occurred in Sabah were committed by immigrants. The interviewees also felt threatened of their own safety in areas that are commonly known as immigrants’ settlements. Despite that, the findings indicate that the interviewees prefer to hire immigrants over migrant workers or the locals. Statistics show that immigrants were involved in crime especially violent crime. There is a need to study further on the economic and social factors that contribute to this phenomenon. While the results of this paper are still preliminary, it helps to clarify some of the myths regarding immigrants’ crimes involvement in Sabah.